‘It is not about punishment, it’s about protection’: Policing ‘vulnerabilities’ and the securitisation of public health in the COVID-19 pandemic - Russell, Emma K. (Criminology & criminal justice, 2024)
This article advances a critical analysis of the concept of ‘vulnerability’ and highlights the ways in which it can work to justify the pre-emptive detention and over-policing of marginalised populations. Building on a historical analysis of the entanglement between public health directives and carceral techniques of securitisation, we provide a contemporary case study of the ‘hard lockdown’ of nine public housing towers in Melbourne, Australia in July 2020, at the start of the city’s second wave of the COVID-19 pandemic. A thematic analysis of media discourses surrounding this event reveals that tower residents were constructed as vulnerable across four interconnecting discourses: spatially, culturally, behaviourally and psychologically. This enabled government actors to frame the exceptional mobilisation of police powers and detention directives to peoples’ homes as caring measures, despite their punitive optics and effects. Our analysis suggests that the pandemic has heightened the securitisation of public health measures, which can extend notions of racial inferiority and pathology, and compound social and economic inequalities. It indicates the need for further interrogation of the nexus between ‘care’ and control and the intensification of police powers in times of crisis.